La importancia de los procedimientos como requisito de S.G.C. Iso 9001:2015 empresa Marecuador, provincia El Oro, Ecuador. - Carrion Jimenez, Jenniffer Marilyn (My University, 2019)
On September 23, 2015, the ISO 9001: 2015 standard was published, which is of vital importance for companies worldwide, nationally and locally, these require compliance with the legal requirements and policies contained in the standard. Previously, the ISO 9001: 2008 standard was used, which was modified so that it is currently based on a new version of 2015 based on processes and principles that must be met by manufacturing and services companies. The Marecuador company located in the province of el Oro, complies in its production processes with the application of the standard specifically in the packaging and weighing process that must comply with quality standards required by ISO 9001:2015. The International quality certification ISO 9001:2015, increases customer satisfaction through improvement processes continues to provide prestige and quality assurance. It focuses within point 7.5. Documented information, within this point is point 7.5.2. When creating and updating the documented information, the organization must ensure that the following is appropriate with respect to its methodology according to the steps used in the process from when the product arrives at the reception until the product reaches its destination at the hands of the customer.
El 23 de septiembre de 2015 se publicó la norma ISO 9001:2015 que es de vital importancia para las empresas a nivel mundial, nacional y local, estas requieren cumplir los requisitos y políticas legales que contiene la norma. Anteriormente se utilizaba la norma ISO 9001:2008 la cual fue modificada para que en la actualidad se base en una nueva versión del año 2015 fundamentándose en procesos y principios que deben cumplir empresas de manufactura y de servicios. La Empresa Marecuador situada en la provincia de El Oro, cumple en sus procesos productivos la aplicación de la norma específicamente en el proceso de empaque y pesado que debe cumplir con estándares de calidad que requiere la Norma ISO 9001:2015. la certificación internacional de calidad ISO 9001:2015, incrementa la satisfacción del cliente mediante procesos de mejora continua brindando prestigio y garantía de calidad. Se enfoca dentro del punto 7.5. Información documentada, dentro de este punto se encuentra el punto 7.5.2. Al crear y actualizar la información documentada, la organización debe asegurarse de que lo siguiente sea apropiado respecto a su metodología de acuerdo a los pasos empleados en el proceso desde que el producto llega a recepción hasta que el producto llegue a su destino a manos del cliente.
Keywords: ISO 9001:2015; EMPRESAS; REQUISITOS